Análise dos impactos da PLP 17/2022 na arrecadação tributária dos estados brasileiros - Araújo, João Borges Castro de (2024)
PLP 17/2022, also known as the Taxpayers’ Statute, is a complementary bill that establishes a code of defense for taxpayers in Brazil. The Code brings together a set of general rules that support, regulate, and discipline the actions and interaction of taxpayers with the Treasury. In Brazil, there is a high degree of heterogeneity between the states in terms of tax collection capacity. In recent years, brazilian states have faced difficulties in closing their public accounts, due to a reduction in federal transfers and an increase in spending. In this sense, against a backdrop of unequal tax collection capacity and fiscal recovery, this study seeks to assess whether the legal adjustments to relations between taxpayers and tax authorities with the implementation of PLP 17/2022 are influencing the states’ tax collection capacity. Therefore, the data on state tax collection from January 2022 to June 2023 is analyzed in order to observe the behavior of the balance of tax collections between the periods before and after the PLP was approved, by applying the econometric model for panel data with Fixed Effects. The results show that in the short term PLP 17/2022, even with a positive effect, has no significant impact on the states’ tax collection behavior.